The Translatability of Emotiveness in Mahmoud Darwish's Poetry - Mahasneh, Anjad (University of Ottawa (Canada), 2010)
This study addresses the translatability of emotive expressions in the poetry of the distinguished Palestinian poet Mahmoud Darwish. The study gives translators and readers an example of how to look at emotiveness in the Arabic poetry by studying main sources of emotiveness like cultural expressions, figures of speech such as rhetorical questions and repetitions as well as expressions of direct emotiveness such as proper names. The ambition of this study is to enrich the literature on translation with new examples of emotiveness by pointing out the expected problem areas when translating emotive expressions. Furthermore, this study is significant since it attempts to answer the question of whether emotiveness constitutes a problem when translating from Arabic into English and whether the meaning and the musicality of poetry are translatable or not. The English translations are selected from: 1. Unfortunately, It Was Paradise translated and edited by Munir Akash and Carolyn Forche with Sinan Antoon and Amira El-Zein (2003) e 2. The Butterfly's Burden translated by Fady Joudah (2007). The original poems can be found in Darwish's most recent poetry collections included in the 2009 edition of The Complete Recent Works by Mahmoud Darwish, published in Beirut. The emotive expressions selected from the English collections and compared to the Arabic original are divided into three categories: the cultural expressions, the linguisticexpressions, and the political expressions. The study highlights different emotive devices used in the selection of poems, by carrying out an analysis of the English translation as well as the Arabic original text. The emotive expressions selected are carefully analyzed to show how the translation was able to render the emotive meaning expressed and intended by the poet in the text in its original form.
Keywords: Literature, Middle Eastern.; Language, General.